Inhibitory Effect of Lomerizine, a Prophylactic Drug for Migraines, on Serotonin-Induced Contraction of the Basilar Artery - Masakazu Ishii; Shunsuke Kobayashi; Masamichi Ohkura; Ryuichi Yamamoto; Shunichi Shimizu; Yuji Kiuchi (Elsevier, 2009)
We examined the effects of lomerizine on serotonin (5-hydroxytryptamine, 5-HT)- induced contraction of the basilar artery and compared them with those of nifedipine. Although both lomerizine and nifedipine completely blocked K+-induced vasoconstriction, 5-HT-induced vasoconstriction was more strongly inhibited by lomerizine than nifedipine. A 5-HT2A antagonist inhibited the 5-HT-induced vasoconstriction, but a 5-HT1B antagonist did not. Lomerizine, but not nifedipine, suppressed 5-HT-induced Ca2+ release in 5-HT2A-expressing HEK293 cells. Moreover, neither antagonist affected ATP-induced Ca2+ release. These results suggest that lomerizine may inhibit not only voltage-dependent Ca2+ channels but also 5-HT2A receptors and so inhibit 5-HT-induced contraction in the basilar artery. Keywords:: lomerizine, serotonin (5-hydroxytryptamine), basilar artery